Vehicle mounted dashboard cameras: a practical approach to GDPR compliance - Kapteinis, Gints (Riga Graduate School of Law, 2021)
Vehicle mounted dashboard cameras or dashcams among other things can be characterized with the growing demand for vehicles around the world. These in size small vehicle innovations are gaining their popularity due to their style, functionality and overall performance. Dashcams and the contents of such perform fundamental sub-tasks that allows for the driver to identify dangerous events and above all protect from potentially unpleasant situations when asked for explanations. It is undoubtable that dashcams can be considered as innovations in their own way, however when exploited for all the wrong reasons such may infringe upon many rights and freedoms of persons concerned. The author of this work explores the concept of dashcam as data processing tool in relation to GDPR compliance. Moreover, the author outlines some of the challenges that data controller may encounter when using a dashcam and above all the relationship between personal interests and the rights and freedoms of the society when evaluating both. The author of this work employs doctrinal as well as comparative research method to reach the conclusion
Embargo periods 4 gadi, kopš 12.05.2021.
Keywords: Data protection; Data controllers